Funding liquidity risk and bank risk-taking in BRICS countries: an application of system GMM approach - Dahir, Ahmed Mohamed; Mahat, Fauziah; Ali, Noor Azman (Emerald Group Publishing, 2018)
Purpose: The purpose of this paper is to examine the effects of funding liquidity risk and liquidity risk on the bank risk-taking. Design/methodology/approach: This study employs a system generalized method of moments (GMM) estimation technique and a sample of 57 banks operating in BRICS countries over the period from 2006 to 2015. Findings: The results reveal that liquidity risk has a significant and negative effect on the bank risk-taking, indicating that a decrease in liquidity risk contributes to higher bank risk-taking. The study also reveals that funding liquidity risk has the substantial impact on bank risk-taking, suggesting lower funding liquidity risk results in higher bank risk-taking. These results are consistent with prior assumptions. Research limitations/implications: The implications of this study highlight the fact that liquidity risk is a risk factor which drives the potential bank default, of which banks tend to take more risks when higher funding liquidity exists. Practical implications: This study offers a number of valuable implications for the policy makers as well as practitioners. The policy makers should take into account better liquidity risk management framework aimed at preventing banks from taking excessive risks. Bank executives must pay more attention on how banks could hold more liquid securities and cash. Less risk-taking reduces higher borrowing costs undermining earnings through imposing taxes on corporate. Originality/value: This work uncovered that liquidity risk per se is an important and previously unidentified risk factor, specifically its effects on bank risk-taking and contributes to the view in support of holding more liquid securities than the past.